Molecular mechanism of the E99K mutation in cardiac actin (ACTC Gene) that causes apical hypertrophy in man and mouse. - Song, W; Dyer, E; Stuckey, D; Copeland, O; Leung, M; Bayliss, C; Messer, A; Wilkinson, R; Tremoleda, J; Schneider, MD; Harding, SE; Redwood, C; et al. (2011)
We generated a transgenic mouse model expressing the apical hypertrophic cardiomyopathy-causing mutation ACTC E99K at 50% of total heart actin and compared it with actin from patients carrying the same mutation. The actin mutation caused a higher Ca(2+) sensitivity in reconstituted thin filaments measured by in vitro motility assay (2.3-fold for mice and 1.3-fold for humans) and in skinned papillary muscle. The mutation also abolished the change in Ca(2+) sensitivity normally linked to troponin I phosphorylation. MyBP-C and troponin I phosphorylation levels were the same as controls in transgenic mice and human carrier heart samples. ACTC E99K mice exhibited a high death rate between 28 and 45 days (48% females and 22% males). At 21 weeks, the hearts of the male survivors had enlarged atria, increased interstitial fibrosis, and sarcomere disarray. MRI showed hypertrophy, predominantly at the apex of the heart. End-diastolic volume and end-diastolic pressure were increased, and relaxation rates were reduced compared with nontransgenic littermates. End-systolic pressures and volumes were unaltered. ECG abnormalities were present, and the contractile response to β-adrenergic stimulation was much reduced. Older mice (29-week-old females and 38-week-old males) developed dilated cardiomyopathy with increased end-systolic volume and continuing increased end-diastolic pressure and slower contraction and relaxation rates. ECG showed atrial flutter and frequent atrial ectopic beats at rest in some ACTC E99K mice. We propose that the ACTC E99K mutation causes higher myofibrillar Ca(2+) sensitivity that is responsible for the sudden cardiac death, apical hypertrophy, and subsequent development of heart failure in humans and mice.